2018
DOI: 10.1080/17430437.2018.1514014
|View full text |Cite
|
Sign up to set email alerts
|

Using football cultures as a vehicle to improve mental health in men: the case of the Redcar and cleveland boot room

Abstract: This paper sets out to appraise (from the perspective of members) the impact of a localised, football-based mental health intervention. Commissioned in late 2015, the 'Redcar and Cleveland Boot Room (BR)' was implemented in response to mass redundancy in the local area, coupled with regional suicide rates in men that exceed the national average. Interactive discussions with BR members revealed that: (a) the language of football and shared identity were important for initiating and sustaining engagement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In a more applied sense, sport settings provide men with the opportunity to socially connect in with community ( Chamravi et al, 2020 ), and can be utilized as men-friendly community settings for health promotion messaging and mental health programs ( Oliffe et al, 2019b ). Programs of this nature that have been developed internationally ( Dixon et al, 2019 ; Wilcock et al, 2021 ), and in Australia have aimed to promote early intervention and help-seeking ( Vella et al, 2018 ; Vella et al, 2021 ), increase parental awareness of mental health ( Hurley et al, 2020 ) and increase men’s self-efficacy, social connectedness, and leadership skills ( Chamravi et al, 2020 ). The implementation of evidence-based programs like this into regional sporting organisations may be a key step forward to increasing belonging and connectedness for many men, and reducing stigma surrounding mental health help-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In a more applied sense, sport settings provide men with the opportunity to socially connect in with community ( Chamravi et al, 2020 ), and can be utilized as men-friendly community settings for health promotion messaging and mental health programs ( Oliffe et al, 2019b ). Programs of this nature that have been developed internationally ( Dixon et al, 2019 ; Wilcock et al, 2021 ), and in Australia have aimed to promote early intervention and help-seeking ( Vella et al, 2018 ; Vella et al, 2021 ), increase parental awareness of mental health ( Hurley et al, 2020 ) and increase men’s self-efficacy, social connectedness, and leadership skills ( Chamravi et al, 2020 ). The implementation of evidence-based programs like this into regional sporting organisations may be a key step forward to increasing belonging and connectedness for many men, and reducing stigma surrounding mental health help-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Dixon et al. () found that sourcing support from a social group or team may enhance mental health, as groups or teams provide a shared identity, language, and structure of accountability for member engagement. In a study of drag performers in the U.S. Southeast, Rogers () found that seeking support from a shared cultural community allows performers to locate information about access to services that are often hidden from dominant view or unavailable to the general public and demonstrates the responsibility that marginalized people often feel to offer support, in its many forms, to those struggling in their communities.…”
Section: Introductionmentioning
confidence: 99%
“…We found two studies describing implementation of (public) awareness raising intervention. One of them was focused on youth (Wasserman et al, 2012 ), and the other targeted male population (Dixon et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The other frequent facilitator was engaging with target group in a way, which is natural and convenient for the target group, i.e. via You Tube, Facebook and other social media, which are used among UK football fans (Dixon et al, 2019).…”
Section: Facilitatorsmentioning
confidence: 99%